AN ANALYSIS OF CLASSROOM INTERACTION PATTERN IN SINGARAJA MONTESSORI SCHOOL (SMS) - ., Aldea Pramesti Angelina; ., Dr. Ni Made Ratminingsih, M.A.; ., Kadek Sintya Dewi, S.Pd., M.Pd. (Universitas Pendidikan Ganesha, 2017)
Interaksi antara siswa dan guru sangat penting didalam pembelajaran. Akan tetapi, tutur guru dan tutur siswa di dalam kelas tidak seimbang. Tutur guru lebih mendominasi tutur siswa, dan hal tersebut mengurangi kesempatan siswa untuk berbicara didalam kelas. Penelitian ini bertujuan untuk mengidentifikasi pola-pola interaksi dan pola dominan di Singaraja Montessori School (SMS). Penelitian ini menggunakan metode deskripsi kualitatif dalam bentuk analisis wacana dengan berpedoman pada kerangka analisis dari Ur (1996). Hasil penelitian ini menunjukkan bahwa terdapat lima pola yang muncul didalam kelas seperti, choral responses, closed-ended teacher questioning, individual work, student initiates – teacher answers, dan teacher talk. Closed-ended teacher questioning merupakan pola dominan di SMS. Pola-pola interaksi dihasilkan dari guru ke siswa, siswa ke guru, dan siswa ke siswa. Hasil ini menunjukkan bahwa proses belajar-mengajar tidak selalu didominasi oleh guru. Para siswa mempunyai peranan aktif dalam berpartisipasi di kelas.Kata Kunci : interaksi kelas, kerangka analisis Ur (1996), metode Montessori, tutur guru dan tutur siswa, wacana kelas Interaction is really important in language teaching. However, the balance between teacher and students talk was not equal. Teacher talk dominated students talk and it decreased students’ chance to talk in the classroom. This study then aimed at identifying the interaction patterns found and the dominant pattern in Singaraja Montessori School (SMS). This study used descriptive qualitative method in form of discourse analysis by using Ur (1996) framework. The findings show that 1) the patterns of interaction emerge in the class are choral responses, closed-ended teacher questioning, individual work, student initiates – teacher answers, and teacher talk, 2) Closed-ended teacher questioning become the dominant pattern in SMS. The patterns of interaction are produced from teacher to student(s), student to teacher, and student(s) to student(s). These patterns are produced constantly. They show that teaching-learning process is not always dominated by the teacher. The students also actively participate in the class.keyword : classroom discourse, classroom interaction, Montessori Method, teacher talk and student talk.